Optimization of fermentation media composition of ganoderma lucidum for improved production of antioxidant and antimicrobial compounds - Singh Paliya, Balwant; Singh Chaudhary, Hotam; Verma, Smrati; Prasad, Shriram (Pharmacognosy Communications)
Introduction: To optimize the fermentation medium for G. lucidum by modifying the Mushroom complete medium (MCM) by three test carbon source Dextrose, Maltose, lactose and five nitrogen sources: peptone, soyapeptone, ammonium chloride (NH4Cl), ammonium nitrate (NH4NO3) and ammonium sulphate (NH4)2SO4 to enhance the production of antioxidant and antimicrobial compounds. Methods: Fifteen different broth medium composition were prepared by varying the carbon and nitrogen sources in test medium (MCM). G. lucidum was cultivated in above test mediums for 7 days. Extraction and quantification of antioxidant compound (exopolysaccharide) and antimicrobial compounds. The antioxidant capacity was determined by three methods: Hydrogen peroxide assay, reducing power assay and hydroxyl radical scavenging assay in vitro while potential of antibacterial compound was determined by Agar well diffusion method. Results: High productivity were seen in medium contained maltose as carbon and soyapeptone, NH4Cl, NH4NO3 as nitrogen source for both exopolysaccharide and antimicrobial compound. The samples demonstrate antioxidant capacity in dose dependent manner in all assays. Scavenging activity of hydroxyl ion (52.7±1.55%) was found potent in medium contained maltose and NH4Cl, which is above than ascorbic acid at same concentration (300 μg/mL). Chloroform: methanol extract shows inhibitory effect to all five human pathogenic strains, potent zone of inhibition was seen against Shigella dysenteriae (16.3±1.69 to 19.6±0.47), Enterococcus facecalis (16.6±1.24 to 20±1.63) and Klebsiella pneumoniae (16.6±1.24 to 21±1.63) which show maximum zone of inhibition (21±1.63). Conclusion: Maltose and NH4Cl are suitable carbon and nitrogen source for antioxidant and antimicrobial compound production.
Keywords: G. lucidum; MCM; exopolysaccharide; antioxidant; antimicrobial compounds; carbon and nitrogen source